Voce e gesto: Gianni Celati e Lino Gabellone traducono Entretiens avec le professeur Y (TEST Ticontre. Theory Text Translation, 2024)
This article examines Gianni Celati and Lino Gabellone's translation of Entretiens avec le professeur Y, a pamphlet written by Louis-Ferdinand Céline and published by Gallimard in 1955. After an initial contextualisation of Céline's work within the modernist movement and a reconstruction of the main peculiarities of Céline's writing, the contribution presents a series of examples of the trans-ductive strategies adopted by the two Italian translators. These analysis will show how, both on the lexical level (thanks to the translators' adoption of a septentrional koiné) and on the level of dialogical rendering (thanks to the performative nature of the translative act) the two translators succeeded in reproducing the characteristics of Céline’s funambolic and agitated prose.